Acessibilidade informacional e comunicacional em editais de ingresso da Educação Superior: um estudo de caso - Braseliano, Luana Alves de Abreu (Universidade Federal de São Carlos, 2024)
Higher Education Institutions (HEIs) are important social historical-cultural spaces, for development, through their teaching, research, extension, management and coexistence activities. However, people with disabilities have found it difficult to access the information that guarantees the materialization of their formal rights to enter, stay and graduate from this level of education. Against this backdrop, the general aim of this research was to identify and analyze, from an accessibility perspective, the communication and information elements that make up undergraduate admission notices. Specifically, the aim was to: (a) identify the main variables that cross-cut the drafting and/or revision of formal documents with a communicational and informational accessibility approach; (b) understand students' perspectives in relation to higher education admission instruments; (c) analyze the facilitating and hindering communicational, informational and technological aspects present in digital assets related to undergraduate admission notices; (d) propose structural, informational, linguistic and technological guidelines for preparing accessible notices. This is a predominantly qualitative case study. Data was collected at the Federal University of São Carlos (UFSCar), both online and in person. The research included the participation of three subjects linked to UFSCar: a disabled undergraduate student, a civil servant responsible for drafting, reviewing and disseminating the public notice and a disabled civil servant involved in the entrance exam boards. The data was processed based on its content and analyzed using the theoretical approach of Institutional Analysis. The results indicate aspects that facilitate and hinder in culture, administration, in the content of the information and in the communication structure of the admissions notice. They are scientifically relevant because they methodologically and theoretically systematize ways of analyzing and improving documents; academically relevant because they enable feedback on a cooperative approach to resolving institutional issues; and socially relevant because they materialize rights proving the population with more access, accessibility and accessibilization.
Informational and communicational accessibility in Higher Education admission notices: a case study
Keywords: Educação especial; Educação superior; Pessoas com deficiência; Direito; Edital; Special education; Higher education; People with disabilities; Law; Notice; CIENCIAS HUMANAS::EDUCACAO